2021
DOI: 10.1002/cti2.1293
|View full text |Cite
|
Sign up to set email alerts
|

Sustained low‐dose interleukin‐2 therapy alleviates pathogenic humoral immunity via elevating the Tfr/Tfh ratio in lupus

Abstract: Objectives Low‐dose interleukin‐2 (IL‐2) has shown promising clinical benefits in the treatment of systemic lupus erythematosus (SLE), but how this therapy alleviates pathogenic humoral immunity remains not well understood. The dilemma is that IL‐2 can suppress both follicular helper and regulatory T (Tfh and Tfr) cells, which counteract each other in regulating autoantibody production. Methods Female NZB/W F1 mice received recombinant human IL‐2 (3 × 104 IU/dose) in three treatment regimens: (1) short, daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…First, the total number of specimens from outpatients with SLE, especially those with active SLE, is limited because the cohort of active SLE patients without drug therapy at the time of study enrolment is small. Several studies have demonstrated that drug treatments can affect cTfh cell frequencies (23,31,41). Therefore, a larger cohort will be investigated to clarify the role of cTfh cell subsets in SLE patients in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the total number of specimens from outpatients with SLE, especially those with active SLE, is limited because the cohort of active SLE patients without drug therapy at the time of study enrolment is small. Several studies have demonstrated that drug treatments can affect cTfh cell frequencies (23,31,41). Therefore, a larger cohort will be investigated to clarify the role of cTfh cell subsets in SLE patients in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty outpatients with SLE and twenty-four age-and sexmatched healthy controls (HCs) were enrolled in the study. SLE patients were recruited according to the American College of Rheumatology criteria for the classification of SLE (23), and the exclusion criteria included therapy with immunosuppressive/ immunomodulant agents. The SLE Disease Activity Index (SLEDAI) scoring system was used to evaluate clinical disease activity, patients were classified according to having inactive or active disease status: the SLEDAI < 6 group comprised subjects with inactive disease (n=17), while SLEDAI ≧ 6 group consisted of subjects with active disease (n=13).…”
Section: Patient Demographicsmentioning
confidence: 99%
“…A balanced IL-2/CD25 signaling is critical for maintaining not just T FR but also T FH generation, because IL-2 could suppress both cells; nevertheless, it is required for Treg development. Two studies demonstrated that a carefully adjusted, prolonged low-dose IL-2 treatment led to the recovery of T FR /T FH immune balance and successfully mitigated pathogenic B cell responses, as well as kidney damage [ 50 , 51 ]. All these results support the use of T FR cells as an attractive therapeutic target in lupus.…”
Section: Discussionmentioning
confidence: 99%
“…HighPD-1 expression on Tfh cells can significantly promote the differentiation and activity of Tfh cells (48)(49)(50). Collectively, Tfh cells are commonly identified as having three phenotypes: canonical GC Tfh cells with PD-1 ++ and ICOS ++ Bcl-6 + CCR7 -CXCR5 ++ CD4 + T cells, precursor-Tfh (Pre-Tfh) cells characterized as PD-1 + ICOS + Bcl-6 low CCR7 low CXCR5 + CD4 + T cells, and memory Tfh cells similar to Pre-Tfh cells in lymphoid tissue (36,(50)(51)(52). In GC, Tfh cells are responsible for regulating B cell differentiation into memory B cells and plasma cells, controlling the selection of high-affinity antibody production and the development of long-term humoral immunity (53)(54)(55)(56).…”
Section: The Phenotypes and Functions Of Tfh Cellsmentioning
confidence: 99%